2013
DOI: 10.1007/s00404-013-2952-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ovarian stimulation on the outcome of intrauterine insemination

Abstract: To sum up, clomiphene stimulation showed to offer significantly lower pregnancy rates in comparison to the natural cycle, FSH stimulation and HMG stimulation in IUI treatment. While women younger than 40 seem not to profit from any ovarian stimulation, women over 40 do profit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
2
12
0
2
Order By: Relevance
“…Our study is consistent with earlier reports with regard to the lack of benefit of CC, LE or HMG alone in ovulatory women undergoing IUI. However, we showed that LE combined with HMG increased the pregnancy and live birth rates in these women.…”
Section: Discussionsupporting
confidence: 93%
“…Our study is consistent with earlier reports with regard to the lack of benefit of CC, LE or HMG alone in ovulatory women undergoing IUI. However, we showed that LE combined with HMG increased the pregnancy and live birth rates in these women.…”
Section: Discussionsupporting
confidence: 93%
“…However, in the HHU and LIN studies, types of ovarian stimulation were distributed equally between the IUI and SRI groups (Table 2), whereas Muharib et al had not used ovarian stimulation at all [10]. Although ovarian stimulation is well known to improve IUI outcome [2, 21], its lack in some cases should not have influenced the main results of this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of conceiving with this infertility treatment depends on several factors, including age, reason for subfertility or infertility, absence/presence and type of ovarian stimulation, as well as the timing of insemination [2]. According to a large retrospective cohort analysis from the Netherlands, covering more than 15,000 IUI-cycles, the mean pregnancy rate was 5.6% per cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the use of a natural cycle involves a reduction of medication costs and the prevalence of multiple pregnancies is lower in comparison to stimulated cycles [63,64]. However gonadotropins stimulated cycles have higher pregnancy rates compared with natural cycles [65].…”
Section: Synchronizing Intrauterine Insemination With Ovulationmentioning
confidence: 99%